Rodzina słowiańskich wyrazów dźwiękonaśladowczych opartych na pierwiastku *gra-. Słowotwórstwo i semantyka - Krystyna Herej‑Szymańska (Annales Universitatis Paedagogicae Cracoviensis. Studia Linguistica, 2023)
Words containing the sound imitation element *gra-, extracted from dictionaries of all Slavic languages and dialects are presented. Their word‑forming development is discussed from interjection through verbs calling the making of this interjection or sounds reminiscent of it, to the names of the activist, i.e. the person who makes this interjection. Then the semantic development of the discussed words is presented. The basic meaning is ‘voice of a crow’, from which the utterance of such or similar voice developed, and then the name of the one who uttered that voice. The second basic meaning in this word family is the sound of something heavy falling on a hard surface. In addition to these basic meanings, which result directly from the association with the sound heard as a gra-, there are more than a dozen secondary meanings, developed in different directions from the basic ones. Formally, this family of words is model. In terms of semantic, however, it is very extensive. A comparative method was used.